Application of the as-4 software in research on players` kinematics on a large area in 3d coordinates as an alternative to commercial programs - Aschenbrenner, P.; Lipinska, P.; Erdmann, W. S. (Baltic Journal of Health and Physical Activity, 2012)
Background: In this work an original computer program for the video analysis of players on a large area by using a single camera is presented. Video analysis is one of the basic research techniques of human movement applied in sport. A set of cameras and special computer software is used for this purpose. Many companies provide hardware and software, but, unfortunately, their high cost and difficulty in usage are their major drawbacks. In order to simplify and reduce the costs of data analysis (obtained from a single camera), AS-4 program was developed.